THE IMPACT OF ZOROASTRIANISM ON SALMAN RUSHDIE’S CREATIVE VISION AND IDENTITY: A STUDY OF MIDNIGHT’S CHILDREN - Prasad, Anjana; Gawai, Vasant Prabhakar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates Salman Rushdie’s strong connection to his Zoroastrian ancestors and demonstrates how he reframes essential ideas in his literature. The method, which focuses on literature like Midnight’s Children, emphasizes Zoroastrian-influenced themes such as dualism, magic, and hybridity. By focusing on specific situations and characters, the analysis exposes subtle degrees of relevance and creative vision, as well as new insights into Rushdie’s cultural and religious background. Rushdie’s novel Midnight’s Children. Zoroaster, the prophet, founded the ancient Persian religion known as Zoroastrianism, which emphasized the concepts of good versus evil, free will, and the ultimate triumph of good. Zoroastrianism plays an important role in the plot since it influences the characters’ attitudes, behaviors, and overall thematic development. The main character, Saleem Sinai, was born on the day India attained independence, and his connection to Zoroastrianism represents the contradictory cultures and identities that exist in post-colonial India. The article looks into the connections between Zoroastrianism and broader subjects like history, identity, and the seeking of meaning in an ever-changing world. Rushdie’s use of Zoroastrianism emphasizes the story’s richness and depth. Rushdie incorporates Zoroastrianism into his literature to demonstrate India’s vast cultural diversity while also adding depth and complexity to the plot. Rushdie’s Zoroastrian upbringing heavily influences his presentation of characters and investigation of topics in Midnight’s Children. The novel becomes a canvas on which Zoroastrian philosophy paints delicate strokes, enhancing the narrative tapestry. Rushdie combines Zoroastrian concepts such as dualism, free choice, and cyclical time into the tale Midnight’s Children. And the story explains how Zoroastrianism influenced Salman Rushdie’s artistic vision and personality. Midnight’s Children explores the complexities of Indian culture and history through its various levels of symbolism and thematic relevance, while also providing a deep exploration of universal human themes and ideas. Zoroastrianism promises redemption through good deeds and spiritual regeneration. Saleem’s voyage, which aligns with Zoroastrian ideals of ethical obligation and divine fairness, can also be interpreted as an attempt at individual and societal healing. Exploring these other dimensions deepens the relationship between Zoroastrianism and Midnight’s Children, offering readers a complex exploration of ethical, intellectual, and Spiritual themes are intertwined throughout India’s rich history and culture